Spaces of Synthesis: Universal Values and Regional Identity in Zlatko Ugljen’s Architecture (Prostor, 2025)
Zlatko Ugljen’s architecture represents a profound engagement with the interplay between regional identity and universal architectural values. Through an analysis of his most significant works, this paper examines how Ugljen synthesizes traditional construction principles with modernist architectural expression, ensuring the continuity of spatial and cultural meaning. Particular attention is given to the concept of the architecture of respect, analyzed within the theoretical frameworks of critical regionalism and the phenomenology of space. Furthermore, the paper investigates the impact of socio-political contexts - ranging from socialist Yugoslavia to the post-conflict reconstruction of Bosnia and Herzegovina - on Ugljen’s architectural practice. Employing a methodological framework that integrates a comparative analysis, case studies, and a phenomenological approach, the paper explores the materiality, spatial organization, and symbolic dimensions of his architectural solutions. The findings suggest that Ugljen’s work serves as a paradigm for contemporary architectural practice, demonstrating how regional identity can be reaffirmed while simultaneously establishing universal spatial values capable of addressing the challenges posed by globalization and cultural fragmentation.